(untitled) (Journal of Science & Technology, 2021)
Legacy systems form the backbone of many industries, yet they often face critical challenges in operational efficiency, reliability, and scalability due to technological obsolescence. These systems, constrained by outdated hardware and software, require innovative strategies to sustain their operational viability and extend their lifespan. This paper investigates the application of artificial intelligence (AI) in predictive maintenance (PdM) as a transformative approach to address these challenges. By leveraging advanced AI models, including machine learning (ML) and deep learning (DL) techniques, predictive maintenance facilitates real-time monitoring, fault prediction, and informed decision-making. These capabilities ensure reduced downtime, enhanced risk mitigation, and optimized asset lifecycle management. The study begins by delineating the complexities inherent in legacy systems, particularly their limited integration with modern data-driven technologies, and explores how AI technologies can bridge these gaps. AI-enabled predictive maintenance strategies are framed within the broader context of Industry 4.0, emphasizing their alignment with digital transformation initiatives. Detailed discussions are presented on key methodologies such as anomaly detection, predictive analytics, and root cause analysis, with particular focus on their adaptability to the unique constraints of legacy systems. For instance, supervised and unsupervised learning algorithms, combined with time-series analysis, have demonstrated significant potential in predicting failures and mitigating risks, despite the limited data availability and heterogeneous configurations typical of legacy infrastructure. A central theme of the paper is the role of hybrid AI models that combine statistical and neural approaches to overcome the limitations posed by noisy, sparse, or incomplete data. Case studies of real-world implementations are reviewed, illustrating how predictive maintenance has successfully enhanced operational efficiency in various industries, including manufacturing, energy, and transportation. For example, neural networks, such as Long Short-Term Memory (LSTM) models, are highlighted for their efficacy in temporal data prediction, enabling proactive measures to avert system failures. Additionally, Bayesian methods and reinforcement learning frameworks are evaluated for their application in decision-making processes under uncertainty, particularly in dynamic operational environments. To address the scalability and deployment challenges associated with legacy systems, this study evaluates edge computing and federated learning paradigms. These technologies enable decentralized AI processing, minimizing latency and ensuring data privacy, which are critical in sectors with stringent regulatory requirements. Furthermore, the integration of digital twin technologies into predictive maintenance workflows is explored as a means of creating virtual representations of legacy systems, facilitating real-time simulation and performance optimization. The study also delves into the economic and operational implications of adopting AI-driven predictive maintenance. Metrics such as mean time to repair (MTTR), mean time between failures (MTBF), and return on investment (ROI) are examined to quantify the benefits of these strategies. Challenges such as resistance to technological change, initial implementation costs, and the need for cross-disciplinary expertise are critically analyzed. Strategies for addressing these barriers, including phased adoption models, stakeholder education, and robust cybersecurity frameworks, are proposed.